A disinhibitory circuit motif and flexible information routing in the brain. (April 2018) - Wang, Xiao-Jing; Yang, Guangyu Robert
Abstract : Highlights: Dendrite-targeting and interneuron-targeting interneurons form a disinhibitory circuit motif. Disinhibitory circuits can perform flexible pathway gating. Dendrite-targeting interneurons are far more abundant in prefrontal cortex. Several distinct gating mechanisms can co-exist in the brain. Abstract : In the mammalian neocortex, an area typically receives inputs from, and projects to, dozens of other areas. Mechanisms are needed to flexibly route information to the right place at the right time, which we term 'pathway gating'. For instance, a region in your brain that receives signals from both visual and auditory pathways may want to 'gate in' the visual pathway while 'gating out' the auditory pathway when you try to read a book surrounded by people in a noisy café. In this review, we marshall experimental and computational evidence in support of a circuit mechanism for flexible pathway gating realized by a disinhibitory motif. Moreover, recent work shows an increasing preponderance of this disinhibitory motif from sensory areas to association areas of the mammalian cortex. Pathway input gating is briefly compared with alternative or complementary gating mechanisms. Predictions and open questions for future research on this puzzle about the complex brain system will be discussed.